2012
DOI: 10.1097/qai.0b013e31825a3668
|View full text |Cite
|
Sign up to set email alerts
|

HIV and Aging

Abstract: HIV risk behaviors, susceptibility to HIV acquisition, progression of disease after infection, and response to anti-retroviral therapy all vary by age. In those living with HIV, current effective treatment has increased the median life expectancy to > 70 years of age. Biologic, medical, individual social and societal issues change as one ages with HIV infection, but there has been only a small amount of research in this field. Therefore, the Office of AIDS Research of the National Institutes of Health commissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
258
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 464 publications
(276 citation statements)
references
References 80 publications
4
258
0
3
Order By: Relevance
“…Possible explanations for a higher mortality risk in older patients include multi‐morbidities, polypharmacy, chronic infection with viral pathogens (e.g. CMV), lower CD4/CD8 ratio, or other age‐related factors, as well as an increased risk of AIDS‐related complications given poor immunologic recovery despite ART 1, 9. A recent study by Edwards et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible explanations for a higher mortality risk in older patients include multi‐morbidities, polypharmacy, chronic infection with viral pathogens (e.g. CMV), lower CD4/CD8 ratio, or other age‐related factors, as well as an increased risk of AIDS‐related complications given poor immunologic recovery despite ART 1, 9. A recent study by Edwards et al .…”
Section: Discussionmentioning
confidence: 99%
“…Older people may have an inaccurate perception of the risk for HIV infection in their peer group and less frequent discussions with medical providers regarding sexual practices and drug use 6, 7, 8. Finally, age‐related changes in the reproductive tract and immune system may enhance susceptibility to HIV acquisition 1, 9.…”
Section: Introductionmentioning
confidence: 99%
“…An increased number of studies draw the attention to the reduction in telomerase length, which is a measure of the proliferation of each single cell, and to mitochondrial damage, which is able to increase oxidative stress and inflammatory pattern, as major drivers for senescence program in all individuals. 7,8,13 Senescence provokes a cascade of morphological and phenotypic changes in cells: a) increase in size and a flat morphology; b) upregulation of tumor suppressor genes and downregulation of cell-cycle promoting genes; c) production of senescence-associated secretory phenotype (SASP), which are inflammatory cytokines, growth factors and matrix metalloproteinases. 8,10,11 In particular Effros et al 8 found an increase in pro-inflammatory cytokines (interleukin-6 [IL-6] and tumor necrosis factor-a [TNF-a]) and a reduction in antiviral interferon-g (IFNg) (released by CD8C T-cells).…”
Section: Immunology Of Aging In Hiv-infected Patientsmentioning
confidence: 99%
“…16 The higher level of inflammation in HIV individuals is measured by inflammatory biomarkers: in particular interleukin-6 (IL-6), C-reactive protein (CRP), D-dimer (DD), cystatin C-dimers and cystatin D-dimers. 7,13,[17][18][19] In HIVinfected individuals these biomarkers are higher than in uninfected adults. They have been studied in HIV patients during HAART and they remain elevated Adapted by permission of James L. Kirkland.…”
Section: Immunology Of Aging In Hiv-infected Patientsmentioning
confidence: 99%
See 1 more Smart Citation